SENSITIVITY OF THE PARAMETRIZED POST NEWTONIAN PARAMETER γPPN TO COSMOLOGICAL MODELS IN STRONG GRAVITATIONAL LENSING - Yasmin Mufidanisa; Agustina Widiyani; Azrul Sulaiman Karim Pohan; Ikah Ning Prasetiowati Permanasari; Annisa Novia Indra Putri (Universitas Mataram, 2026)
The parametrized post-Newtonian (PPN) parameter γ measures spacetime curvature per unit gravitational potential, with general relativity (GR) predicting γ = 1 exactly. Strong gravitational lensing at galactic scales offers a cosmological-scale avenue for estimating γ beyond solar system experiments; however, such estimates depend sensitively on angular diameter distances, which in turn depend on the assumed cosmological model. We perform a controlled sensitivity analysis using 40 Sloan Lens ACS (SLACS) strong lensing systems with catalogue SIE Einstein masses MEin fixed under a fiducial ΛCDM cosmology, while varying the background model across ΛCDM, wCDM, Dynamical Dark Energy (DDE), and Early Dark Energy (EDE), all adopting Planck 2018 parameters. Angular diameter distances are computed by numerically integrating the model-specific expansion function E(z), so that any variation in recovered γPPN reflects cosmological distance geometry rather than a gravitational signal. ΛCDM, wCDM, and DDE yield effectively degenerate estimates: mean γ ≈ 1.08 ± 0.020, with inter-model spread of only 0.5–0.7%. EDE yields a systematically lower mean γ = 0.903 ± 0.019, approximately 16.3% below ΛCDM and below the GR prediction of unity. This shift arises because EDE elevates H(z) near matter-radiation equality (z 3000), compressing angular diameter distances by 10% relative to ΛCDM; since the γ estimator scales as DL × DS / DLS, this compression propagates into a downward shift in recovered γ. The total inter-model range of 17% substantially exceeds statistical uncertainties in targeted lensing studies, establishing cosmological model selection as a leading systematic in lensing-based γ measurements. EDE in particular introduces a distinctive geometric signature not captured by late-time dark energy parameterizations. Because MEin is fixed under ΛCDM, these findings should not be interpreted as evidence for or against GR, but as a geometric sensitivity analysis within a specific set of modeling assumptions.